Whole Exome Sequencing Identifies Atypical Welander Distal Myopathy in Patient. Issue 3 (March 2017) - Gass, Jennifer; Blackburn, Patrick; Jackson, Jessica; Harris, Kimberly; Selcen, Duygu; Dimberg, Elliot; Atwal, Paldeep
Abstract : Abstract: Welander distal myopathy is a rare autosomal dominant disorder characterized by muscle weakness in the hands and feet. Exome sequencing of affected families discovered a segregating p.Glu384Lys pathogenic variant in TIA-1 as the main genetic cause of Welander distal myopathy. TIA-1 encodes an RNA-binding protein which serves as a key component of stress granules. This protein also regulates splicing and translation of mRNA. Our patient developed progressive weakness in his hands and feet during his late 40s that was misdiagnosed as a neuropathy that caused muscle atrophy. Follow-up genetic testing revealed a p.Glu384Lys pathogenic variant in TIA-1, and he was then diagnosed with Welander distal myopathy. Our case report underlines the importance of electrodiagnostic and genetic testing of patients.